PENGARUH PERTUMBUHAN PERUSAHAAN TERHADAP STRUKTUR MODAL DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Empiris Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2013 - 2016) - Neni Pitriyani; Wawan Ichwanudin; Enis Khaerunisa (Tirtayasa Ekonomika, 2018)
The aimed of this study is to investigate whether the company’s growth affect the capital structure, using profitability is able to intervening variable. In this study, the capital structure is measured by debt to equity, company growth measured by sales growth, and profitability measured by return on assets.In addition, the population obtain from food and beverage company which are listed on the Indonesian Stock Exchange (IDX) from 2013-2016 and the limitations gathered 13 firms-years observation as population. The analytical method are using outlier test, classic assumption test, partial test (t test) and path analysis.From hypotesis results by using t test and path analysis show that : 1) company’s growth has a positive significant effect on profitability. 2) company’s growth has no effect on capital stucture 3) profitability has a negatif and significant effect on capital stucture 4) profitability can not be intervening the relationship of company’s growth and capital stucture.Keywords:       Company Growth, Profitability, Capital Structur